THE CORRELATION OF LOWER URINARY TRACT SYMPTOMS (LUTS) ON BENIGN PROSTATIC HYPERPLASIA (BPH) PATIENTS AND ERECTILE DYSFUNCTION IN RADEN MATTAHER HOSPITAL JAMBI - Ismiyanti, Anissa; Fauzan, Randy; Periadi, Ardiansyah; Herman, Hendra; Rachman, Wendi; Herlambang; Dewi, Hasna (Indonesian Urological Association, 2023)
Objective: This study aims to determine the relationship between Lower Urinary Tract Symptoms (LUTS) in patients with Benign Prostatic Hyperplasia (BPH) and erectile dysfunction at Raden Mattaher Hospital Jambi. Material & Methods: This research is an observational analytic with a cross sectional approach. The sample of this study includes 48 people using total sampling technique. Data analysis was carried out to test the hypothesis by the Spearman correlation test. Results: Based on the results of the Spearman correlation test analysis showed that there was a statistically significant relation (p=0.000) between Lower Urinary Tract Symptoms (LUTS) in patients with Benign Prostatic Hyperplasia (BPH) and erectile dysfunction. Conclusion: There is a significant relation between Lower Urinary Tract Symptoms (LUTS) in patients with Benign Prostatic Hyperplasia (BPH) and erectile dysfunction at Raden Mattaher Hospital Jambi.